Duodenum Inversum: A Rare Cause of Chronic Nausea and Vomiting - Saurabh Chandan; Ojasvini Choudhry Chandan; Alexander Todd Hewlett (Case Reports in Gastrointestinal Medicine)
Duodenum inversum (DI), also known as inverted duodenum or duodenum reflexum, is a congenital malformation in which the third portion of the duodenum, instead of continuing leftward to the ligament of Treitz, reverses direction and travels in a superior, posterior track prior to crossing the midline above the pancreas. We present a case of a 62-year-old woman presenting with chronic nausea and vomiting, subsequently found to have DI.